The persuasive effects of verbal anchoring and visual complexity. Issue 1 (2nd January 2022) - Bünzli, Fabienne; Dillard, James Price
Abstract: Many persuasive messages intermingle images with text. Readers who wish to interpret such messages must grapple with the information in both modalities as well as the relationship between them. One instance of this occurs in modern advertising, which is predominantly visual with verbal text assuming a supporting role. The text functions to anchor the meaning of the image, thereby guiding the reader to the preferred conclusion. However, little is known about how variations in verbal anchoring produce meaning and persuasion. To address this knowledge gap, the present study sketches a model of message processing in which perceived interpretational guidance is the key explanatory mechanism. A repeated measures experiment ( N = 304) finds that verbal anchoring (complete vs. moderate vs. none) is positively related to perceived interpretational guidance, regardless of the complexity of an ad's image (straightforward vs. visual rhetorical figure). Moreover, perceived interpretational guidance explains the effects of verbal anchoring on persuasion. Findings suggest that complete anchoring should be preferred over moderate or no anchoring because people value the cognitive efficiency associated with being guided in their interpretation of the ad's visual imagery.